Estudio de factibilidad y diseños definitivos del sistema de alcantarillado sanitario y pluvial del recinto San José del Recreo, perteneciente al cantón Camilo Ponce Enríquez. - Gía Belduma, Freddy Fernando (2015)
Campus San José del Recreo belonging to the Canton Camilo Ponce Enriquez, Azuay Province, has the drinking water but not with the service Sanitary Sewer and Stormwater, not having these systems Sanitation those grounds have been suffering diseases infectious not be where wastewater discharge in this project we will solve this problem to improve the quality of life of local people and their daily activities and develop normally. This project or study is supported in constructive MIDUVI standards in bibliographic research and on the web, which will have a greater knowledge of implementation and laying the pipes with diameters corresponding according to the calculation performed. The project has the plans, reference budget and technical specifications. The results obtained according to the procedures were employed and calculated to optimize and reduce costs for the construction of the systems, plus a maintenance manual thereof shown, allowing optimal and responsible management that extends the useful life of the work.